The Role of the Cooperatives and SMEs Office in Empowering Small and Medium Enterprises in Medan City (Study at the North Sumatra Province Cooperatives and SMEs Office) - Wina Aprillia; Sri Sudiarti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The role department of Cooperatives and UKM of North Sumatra province, one of which is to empower the UKM in the city of Medan has been contained in the RENSTRA of the Department of Cooperatives and UKM of North Sumatra province. The efforts made by the Department of Cooperatives and UKM of North Sumatra province are expected encourage of UKM as an economics power that can improve the welfare and prosperity of the lower and middle class people in Medan City. The purpose of this research is determine the implementation of the UKM empowerment in the Medan City with supporting factors and inhibiting factors. This research uses a descriptive research method using a qualitative approach. The data collection technique uses literature study, observation, interviews, and documentation. The informants used in this research amounted to five people. This research focuses in the implementation of UKM empowerment with supporting factors and inhibiting factors. The results of the research indicate that the empowerment of UKM in the Medan city has been running well and effectively with supporting factors and inhibiting factors. The advice given is the Department of Cooperatives and UKM of North Sumatra province should further optimize its role in empowering UKM, by means of prioritizing empowerment it must first identify UKM based on their level of empowerment and powerlessness in order to optimize the empowerment of UKM in Medan City.